MONITORING KEGIATAN REBOISASI KEBUN RAYA BALI TERHADAP TANAMAN LANGKA DAN BERPOTENSI DI BEBERAPA KABUPATEN TABANAN DAN BULELENG, BALI - PUTRI, DYAN M. S.; FAUZI, AHMAD (Jurnal Biologi Udayana; Vol 22 No 2 (2018): JURNAL BIOLOGI UDAYANA, 2018)
Changes in the function of forest land can lead to the existence of even unique endemic species threatened with extinction in nature. Reforestation and monitoring activities were conducted to determine the condition of the crop (plant growth and the percentage of growing plants) so that it can be anticipated the way of handling it and follow up the next activity. Reforestation activities have been conducted since 2003 and monitoring activities were conducted within four years from 2013 to 2016. The location of the activities was done in several planting locations in Tabanan and Buleleng districts. The material used was 36 types of plants that are the result of Bali Botanic Gardens propagation. Data obtained in the form of percentage data of life and plant height (meters) and analyzed descriptively. From the results of this activity it was known that the success rate of successful reforestation plant of selected species were Dacrycarpus imbricatus (Blume) de Laubenf 72%, Elaeocarpus grandiflorus J.E.Sm. 70%, Michelia champaca L. 73%; berulang and Casuarina junghuhniana Miq. 56%. This activity is also expected to save Dacrycarpus imbricatus (Blume) de Laubenf, Elaeocarpus grandiflorus J.E.Sm., and Michelia champaca L.